The characterization of mobile colistin resistance (mcr) genes among 33 000 Salmonella enterica genomes from routine public health surveillance in England. Issue 2 (31st January 2020) - Sia, Cheryll M.; Greig, David R.; Day, Martin; Hartman, Hassan; Painset, Anais; Doumith, Michel; Meunier, Daniele; Jenkins, Claire; Chattaway, Marie Anne; Hopkins, Katie L.; Woodford, Neil; Godbole, Gauri; et al.
Abstract : To establish the prevalence of mobile colistin resistance ( mcr ) genes amongst Salmonella enterica isolates obtained through public health surveillance in England (April 2014 to September 2017), 33 205 S . enterica genome sequences obtained from human, food, animal and environmental isolates were screened for the presence of mcr variants 1 to 8. The mcr -positive genomes were assembled, annotated and characterized according to plasmid type. Nanopore sequencing was performed on six selected isolates with putative novel plasmids, and phylogenetic analysis was used to provide an evolutionary context for the most commonly isolated clones. Fifty-two mcr -positive isolates were identified, of which 32 were positive for mcr-1, 19 for mcr-3 and 1 for mcr-5 . The combination of Illumina and Nanopore sequencing identified three novel mcr-3 plasmids and one novel mcr-5 plasmid, as well as the presence of chromosomally integrated mcr-1 and mcr-3 . Monophasic S. enterica serovar Typhimurium accounted for 27/52 (52 %) of the mcr -positive isolates, with the majority clustering in clades associated with travel to Southeast Asia. Isolates in these clades were associated with a specific plasmid range and an additional extended-spectrum beta-lactamase genotype. Routine whole-genome sequencing for public health surveillance provides an effective screen for novel and emerging antimicrobial determinants, including mcr . Complementary long-read technologies elucidated the genomic context of resistance determinants, offering insights into plasmid dissemination and linkage to other resistance genes.